LINCOLN, NEB., REVISED ORDINANCES, pt. 2, ch. 14, art. 26, § 2 (State Journal Company, Printers 1895). - (:unkn) unknown (General Publisher, 1895)
No person shall sell, loan, or furnish, to any minor, any gun, fowling-piece, or other fire-arm, within the limits of the city, under penalty of a fine of fifty dollars for each offense.
--
Keywords: TRANSFER ONLY